2019
DOI: 10.1002/cam4.2025
|View full text |Cite
|
Sign up to set email alerts
|

Metformin reduces prostate cancer risk among men with benign prostatic hyperplasia: A nationwide population‐based cohort study

Abstract: Benign Prostate Hyperplasia (BPH) has been associated with prostate cancer prevalent among men after 50 years of age, however, it is unclear whether the antidiabetic drug, metformin, can reduce prostate cancer for men with BPH. The insurance claims data of men aged 50 years or older, with both type 2 diabetes mellitus (T2DM) and BPH diagnosed from 1997 to 2007 were analyzed. Individuals were followed up for at least 5 years. We identified 2906 and 2906 patients as the metformin cohort and nonmetformin cohort, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 54 publications
(118 reference statements)
0
15
0
3
Order By: Relevance
“…21,22 Beyond its antidiabetic role, metformin treatment is associated with decreased cancer incidence and as well decreased cancer-related mortality. 23,24…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Beyond its antidiabetic role, metformin treatment is associated with decreased cancer incidence and as well decreased cancer-related mortality. 23,24…”
Section: Introductionmentioning
confidence: 99%
“…with metformin reduced the risk of prostate cancer in men with type 2 diabetes and BPH (adjusted HR of 0.69 (95% CI 0.49, 0.96)) 9 but found a similar effect of traditional Chinese medicine which also points to a non-causal explanation. Thus, this issue remains unsettled.…”
Section: Open Accessmentioning
confidence: 90%
“… 29 Similarly, another systematic review included a comprehensive bias evaluation and concluded that the studies least likely to be affected by bias did not support a causal effect of metformin on cancer risk. 30 A recent Taiwanese study found that treatment with metformin reduced the risk of prostate cancer in men with type 2 diabetes and BPH (adjusted HR of 0.69 (95% CI 0.49, 0.96)) 9 but found a similar effect of traditional Chinese medicine which also points to a non-causal explanation. Thus, this issue remains unsettled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudos sugerem que a metformina pode estar associada à redução no risco de câncer (DABROWSKI et al, 2017;KIM et al, 2018;KUO et al, 2019;WEN et al, 2019;YAO et al, 2019;YE et al, 2019) e a melhores prognósticos em pacientes com câncer (GUO et al, 2017;LI et al, 2017b;WAN et al, 2018;SHI et al, 2019).…”
Section: Diabetes Mellitusunclassified